Effectiveness Of The Implementation Of The Blud Financial Management Model (Ppk-Blud) On The Financial Performance Of Government Hospitals In Indonesia : A Systematic Review - Grace Yohana; Yesiana Situmorang; Dwi Noerjoedianto; Arnild Augina Mekarisce (CV. AFDIFAL MAJU BERKAH, 2026)
The implementation of the Regional Public Service Agency Financial Management Model (PPK-BLUD) is a form of public sector financial management reform that aims to improve the flexibility, efficiency, and accountability of government hospital financial performance. This study aims to examine the impact of BLUD implementation on the financial performance of government hospitals in Indonesia. This study uses a literature review approach to empirical articles that discuss hospital financial performance before and after the implementation of BLUD in Indonesia. The selection process was carried out through stages of identification, screening, and feasibility until nine relevant full-text articles were obtained. The results of the study show that, in general, the implementation of BLUD has a positive impact on increasing revenue and certain financial ratios, especially profitability and liquidity. However, several studies found that this increase was not evenly distributed across all indicators, particularly profitability and service performance. These findings indicate that the success of BLUD implementation is greatly influenced by the quality of financial management, human resource competencies, and the optimization of flexibility provided by regulations.